MODEL PEMBELAJARAN SNOWBALL THROWING PADA PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - putri aulia (Universitas Sriwijaya, 2014)
Abstract: The purpose of this study was to improve student learning outcomes through the learning model of Snowball Throwing at the fourth grade Elementary School 179 Palembang . This study uses classroom action research with the subject of this study was grade IVA Elementary School 179 Palembang Semester 2013/2014 school year, amounting to 25 students , consisting of 12 male students and 13 female students. The results showed an increase in the average value and mastery learning . In the first cycle increased compared to pre-cycle value that is from 65 to 74.1 with the percentage of completeness 44 % to 64 % . Then the average value of the second cycle of the first cycle is increased from 74.1 to 84.22 percentage of completeness becomes 64 % to 84 % . The percentage of the average activity of the students also increased , the percentage of active students in the first cycle to the second meeting of the first meeting of which 62.4 % ( Quite Active ) to 69 % ( Active ) . Furthermore , the percentage of active students increased in the second cycle of the first cycle , the first meeting of which 75 % ( Active ) increased at the second meeting , namely 83.2 % ( Highly Active ) . After conducting action research , it can be concluded that the model of Snowball Throwing learning can improve student learning outcomes in thematic learning.Keywords: Learn, The Learning Result, Snowball Throwing Learning Model, Tematic Learning Abstrak: Tujuan penelitian ini adalah untuk meningkatkan hasil belajar siswa melalui model pembelajaran Snowball Throwing di kelas IV SD Negeri 179 Palembang. Penelitian ini menggunakan Penelitian Tindakan Kelas dengan subjek penelitian ini adalah siswa kelas IVA SD Negeri 179 Palembang Semester Genap Tahun Ajaran 2013/2014 yang berjumlah 25 orang siswa, terdiri dari 12 orang siswa laki-laki dan 13 orang siswa perempuan. Hasil penelitian ini menunjukkan terjadinya peningkatan nilai rata-rata dan ketuntasan belajar. Pada siklus I meningkat dibanding nilai pra siklus yaitu dari 65 menjadi 74,1 dengan persentase ketuntasan 44% menjadi 64%. Kemudian nilai rata-rata siklus II meningkat dari siklus I yaitu dari 74,1 menjadi 84,22 dengan persentase ketuntasan 64% menjadi 84%. Persentase keaktifan rata-rata siswa juga mengalami peningkatan, dari persentase keaktifan siswa pada siklus I pertemuan pertama ke pertemuan kedua yaitu 62,4% (Cukup Aktif) menjadi 69% (Aktif). Selanjutnya, persentase keaktifan siswa pada siklus II meningkat dari siklus I, pertemuan pertama yaitu 75% (Aktif) meningkat pada pertemuan kedua yaitu 83,2% (Sangat Aktif). Setelah melaksanakan penelitian tindakan kelas, dapat disimpulkan bahwa model pembelajaran Snowball Throwing dapat meningkatkan hasil belajar siswa pada pembelajaran tematik.Kata Kunci: Belajar, Hasil Belajar, Model Pembelajaran Snowball Throwing, Pembelajaran Tematik